Digitalization of central bank money : Effects on governance, financial stability, and monetary policy - Litmanen, Elmeri (My University, 2024)
In this thesis we study digitalization of central bank money and its effects on governance, financial stability, and monetary policy of a central bank. The study is conducted with a literature review as a research method. The aim of the literature review is to help gaining a comprehensive understanding of the latest state of the CBDC research within our research objectives. Central bank currency is disappearing, and new private financial systems have become more popular. Due to this, central banks are developing a digital alternative for central bank issued money named central bank digital currency (CBDC), which could increase the resilience of the payment systems, allow new control mechanisms for central banks, and offer new functionalities for the end users. Balance sheet dynamics of CBDC depend on its design. Converting bank deposits to CBDC causes bank disintermediation, which creates liquidity risk when banks conduct maturity transformation under fractional reserve system. The loss of deposits restrains bank funding which leads to contraction in bank lending and reduction in investments in the economy. The risk of bank disintermediation depends on the competitiveness of the banking sector and the interest paid to CBDC. The more market power banks have, the less introduction of CBDC leads to contraction of banks’ balance sheets. A moderate CBDC rate may even expand bank credit due to increased demand for saving and improved financial inclusion in the developing countries. Central banks have two ways to mitigate the risk of bank disintermediation with balance sheet dynamics. First, if households choose to convert assets to CBDC, central banks have a way to offset the contraction of bank deposits by purchasing treasury assets from households. Second, central banks can substitute lost bank deposits with central bank funding. However, this changes optimal choices of agents in the economy unless liquidity and wealth neutrality holds. Also, this implies that central bank becomes a financial intermediator that is subject to risks of maturity transformation. Other ways to mitigate the risk of bank disintermediation are controlling the attractiveness of CBDC with two-tiered remuneration and limitations in payment efficiency, although these have the potential to undermine the functions of CBDC as a store of value and a medium of exchange. Introducing CBDC as an extension to reserves system impacts monetary policy transmission. When CBDC and reserves are subsumed, non-bank financial institutions are granted access to CBDC. Setting the monetary policy instrument can produce central bank balance sheet expansion. The effectiveness of monetary policy transmission could be amplified with CBDC to the short-term and long-term interest rates via bank lending channel. However, the more the transmission improves, the less impactful the lending channel may become as this happens when demand for CBDC increases. CBDC could be introduced without the risk of bank disintermediation if the following is considered: Remuneration rate on CBDC should fluctuate for market clearing to take place with CBDC in price parity with bank deposits. Central bank should hold CBDC and reserves separate, banks should not guarantee convertibility from demand deposits to CBDC, and central banks should be able to define which assets can be converted with CBDC.
Keywords: CBDC, financial stability, bank disintermediation, monetary policy transmission